TROPHIC ECOLOGY OF SHORT-TOED TREECREEPER’S CERTHIA BRACHYDACTYLA (BREHM, 1820) NESTLING IN THE SUBURBAN AREA OF ELHARRACH (ALGERIA) - B. A. Boulaouad; O. Ailam; S. Daoudi-Hacini; S. Doumandji. (Journal of Animal and Plant Sciences, 2018)
In this paper we are studing the diet composition of the short-toed treecreeper’s Certhia brachydactyla (Brehm, 1820) nestling in the suburban area of El Harrach (Algeria). The diet analysis is based on examining fecal sacs which were carried out by parents and placed on the bark of Washingtonia robusta and Jacaranda mimosifolia near the nest during the breeding season 2014/2015. Fecal sacs were collected and treated separately in 70% alcohol to identify prey-species. In total, 277 items, representing 66 prey-species were identified from the collected fecal sacs of short-toed treecreeper nestling. The relative abundance index revealed that the insects were dominants with 67.15%, followed by arachnids 27.44%, Gastrapoda 3.61% and the other classes were poorly represented. Regarding the order of the different class-preys, the diet consisted predominantly of Araneae with (27.44%), followed by Coleoptera (24.91%) and Hymenoptera (18.05%). For the prey size, it varied from 1 mm to 15 mm with an average of 4.33±0.13 mm. And the most represented prey measuring was between [2,55-4,11 mm].
Keywords: short-toed tree creeper; diet; fecal sac; nestling; prey size